Lactylation of PD-L1 by a lactyltransferase HAT1 dictates its protein stability and tumor immune evasion - Man Shang; Xujie Zhao; Yibi Zhang; Chang Zhang; Xiaohui Yang; Ya Wen; Xiaofeng Zhu; Yiwen Chen; Yinmin Gu; Yongbo Pan; Siyuan Jiang; Shuguang Tan; et al. (Proceedings of the National Academy of Sciences, 2026)
Lysine lactylation regulates protein fate and function across diverse biological processes. While PD-L1 has been widely studied posttranslationally, the role of its lactylation and the responsible enzyme have remained poorly studied. Here, we identify histone acetyltransferase 1 (HAT1) as a lactyltransferase that catalyzes programmed cell death ligand 1 (PD-L1) lactylation at residues K75 and K178 within its extracellular domain, thereby enhancing PD-L1 stability. Mechanistically, this glycosylation-dependent modification protects PD-L1 from endoplasmic reticulum (ER)-associated degradation and promotes ER-to-Golgi trafficking. Targeting PD-L1 lactylation by HAT1 knockdown, mutation of the lactylation sites or HAT1-PD-L1-interferring peptides suppresses tumor progression and enhances anti-PD-1 therapy efficacy. Clinically, lactylated PD-L1 strongly correlates with tumor progression. Together, these findings establish HAT1-mediated PD-L1 lactylation as a key mechanism of immune evasion and suggest that targeting this pathway could improve cancer immunotherapy outcomes.